2014
DOI: 10.1002/cncr.29207
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration pneumonia after concurrent chemoradiotherapy for head and neck cancer

Abstract: Background Aspiration pneumonia represents an under-reported complication of chemoradiotherapy in head-and-neck cancer. This study evaluated the incidence, risk factors, and mortality of aspiration pneumonia in a large cohort of head-and-neck cancer patients treated with concurrent chemoradiotherapy. Methods Patients with head-and-neck cancer diagnosed between 2000 and 2009 were identified from the SEER-Medicare database. Aspiration pneumonia was identified from Medicare billing claims. The cumulative incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
124
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 33 publications
12
124
3
4
Order By: Relevance
“…Second, differential diagnosis between aspiration pneumonia and other types of pneumonia was often difficult because the definitions of aspiration pneumonia varied among previous reports [911]. Third, the median follow-up of 2.4 years was shorter than in previous studies [4, 7]. The ability of our predictive model might change upon a long-term follow-up.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Second, differential diagnosis between aspiration pneumonia and other types of pneumonia was often difficult because the definitions of aspiration pneumonia varied among previous reports [911]. Third, the median follow-up of 2.4 years was shorter than in previous studies [4, 7]. The ability of our predictive model might change upon a long-term follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…Several risk factors for aspiration pneumonia in patients with HNC after CRT were reported in previous studies [7, 9, 17]. However, evaluation of the long-term risk factors was often difficult in patients with HNC because these patients’ characteristics varied according to the multimodal therapies that they had received, including surgery, CRT, and RT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dysphagia in particular appears most highly correlated with long-term functional and quality of life outcomes [1517]. A recent SEER analysis provided population-level evidence that an alarmingly large proportion of head and neck cancer patients develop aspiration pneumonia (i.e., 23.8% 5-year aspiration pneumonia risk after chemoradiation) resulting in substantial morbidity and excess mortality [18]. Due in part to these toxicity and quality of life concerns, it is clear that prospective collection of both functional and patient-reported outcomes (PROs) is imperative if valid comparisons are to be made between treatment algorithms and patients are to be counseled appropriately on their therapeutic options [1922].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe RAD may require lifelong tube feeding[5], or suffer potentially life-threatening aspiration[3, 4]. Population level data suggest 3-fold elevated risk of aspiration pneumonia in head and neck cancer (HNC) patients treated with chemoradiotherapy (CRT) relative to non-cancer controls, and 42% excess mortality among cancer survivors who develop pneumonia[6]. Pooled analysis of Radiation Therapy Oncology Group (RTOG) trials of CRT for HNC reported unacceptably high rates of severe late toxicity (i.e., 43% of patients with adequate baseline function had grade 3–4 late laryngopharyngeal toxicity) suggesting that further dose intensification cannot be safely achieved without new technique(s) to protect against late effects[7].…”
Section: Introductionmentioning
confidence: 99%